Implementation of web product search engine : multimodal query suggestion - Mok, Clarence Bao Ren. (2011)
The goal of autosuggestion and preview in search engines is to give the user a more convenient and comprehensive search experience as search terms that are valid in the system can be displayed to the user and previews provide useful visuals to the user as well.